Social Media Development in Herbal Soup Culinary Business in Batam City - Giorgyna Giorgyna; Edy Yulianto Putra; Renza Fahlevi; Kelfi Yanti Limanda; Nida Ohanna (International Journal of Economics, Business and Innovation Research, 2023)
L & D Herbal soup is an MSME engaged in the culinary field that was taken over in 2020, after being affected by the Covid-19 virus outbreak. L & D soup which has the opportunity to be able to increase their sales by developing on social media. The purpose of this study is to examine the impact of social media development on market segmentation, uploaded content, and the effectiveness of social media promotional marketing strategies. The author hopes that this writing can provide suggestions and input that can help the smooth running of the L&D Herbal Soup business. The benefit of this writing is to provide marketing strategies through social media networking platforms and assist in market segmentation, so that L&D Herbal Soup becomes better known. This study uses a qualitative data collection method in the form of a questionnaire. Descriptive analysis techniques are used to process the data obtained previously. Based on the findings of this study, the development of L & D Herbal Soup social media is effective and efficient. Because Soup Herbal social media allows potential customers to see a list of available menus. In addition, compared to before posting, the number of visits to Sop Herbal's Instagram has increased significantly.